Systemic and Cardiac Alterations After Long Bone Fracture - Weber, Birte; Lackner, Ina; Knecht, Deborah; Braun, Christian Karl; Gebhard, Florian; Huber-Lang, Markus; Hildebrand, Frank; Horst, Klemens; Pape, Hans Christoph; Ignatius, Anita; Schrezenmeier, Hubert; Haffner-Luntzer, Melanie; et al. (Shock, 2020)
The purpose of this study was to reveal possible consequences of long-bone fracture on cardiac tissue and to analyze the role of systemically elevated danger associated molecular patterns, complement anaphylatoxins and cytokines. Blood samples of mice, pigs, and humans after a fracture were analyzed by ELISAs for complement component 5a (C5a), tumor necrosis factor (TNF), and extracellular histones. In vivo results were completed by in vitro experiments with human cardiomyocytes treated with TNF and extracellular histones. The influence of histones and human plasma after fracture on isolated human polymorphonuclear leukocytes (PMNs) was investigated. An elevation of TNF, C5a, and extracellular histones after long bone fracture was measured. Moreover, the appearance of systemic troponin I levels was observed and structural changes in connexin 43 and desmin were detected. Further, the presence of TNF leads to elevation of reactive oxygen species, troponin I release, and histone appearance in supernatant of human cardiomyocytes. Incubation of human PMNs with histones and plasma of patients after fracture lead to formation of neutrophil extracellular traps. Present results suggest that structural alterations in the heart might be consequences of the complement activation, the release of extracellular histones, and the systemic TNF elevation in the context of a long bone fracture.
CRIS-Team Scopus Importer:2020-12-21